Subfunctionalization of Duplicated Zebrafish pax6 Genes by cis-Regulatory Divergence - Kleinjan, Dirk A (Public Library of Science, 2008)
Gene duplication is a major driver of evolutionary divergence. In most vertebrates a single PAX6 gene encodes a transcription factor required for eye, brain, olfactory system, and pancreas development. In zebrafish, following a postulated whole-genome duplication event in an ancestral teleost, duplicates pax6a and pax6b jointly fulfill these roles. Mapping of the homozygously viable eye mutant sunrise identified a homeodomain missense change in pax6b, leading to loss of target binding. The mild phenotype emphasizes role-sharing between the co-orthologues. Meticulous mapping of isolated BACs identified perturbed synteny relationships around the duplicates. This highlights the functional conservation of pax6 downstream (3′) control sequences, which in most vertebrates reside within the introns of a ubiquitously expressed neighbour gene, ELP4, whose pax6a-linked exons have been lost in zebrafish. Reporter transgenic studies in both mouse and zebrafish, combined with analysis of vertebrate sequence conservation, reveal loss and retention of specific cis-regulatory elements, correlating strongly with the diverged expression of co-orthologues, and providing clear evidence for evolution by subfunctionalization.